2004
DOI: 10.1111/j.1939-1676.2004.tb00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Cortical Degeneration in Adult American Staffordshire Terriers

Abstract: Adult-onset cerebellar cortical degeneration recently has been reported in American Staffordshire Terriers. We describe the clinical and histopathologic features of this disease and examine its mode of inheritance in 63 affected dogs. The age at which neurologic deficits 1st were recognized varied from 18 months to 9 years, with the majority of dogs presented to veterinarians between 4 and 6 years of age. Time from onset of clinical signs to euthanasia varied from 6 months to 6.5 years, with the majority of af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
0
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 26 publications
6
77
0
7
Order By: Relevance
“…These changes fit well with previous reports of CCD or cerebellar abiotrophy, where primary Purkinje neuron loss and secondary granular cell degeneration are most commonly reported [7, 11, 13, 14, 16]. Similar to previous studies, the HVs also demonstrated a characteristic distribution of cerebellar folial atrophy, with the dorsal and rostral vermis predominantly affected whilst the caudoventral regions appeared spared [10, 12, 14, 17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These changes fit well with previous reports of CCD or cerebellar abiotrophy, where primary Purkinje neuron loss and secondary granular cell degeneration are most commonly reported [7, 11, 13, 14, 16]. Similar to previous studies, the HVs also demonstrated a characteristic distribution of cerebellar folial atrophy, with the dorsal and rostral vermis predominantly affected whilst the caudoventral regions appeared spared [10, 12, 14, 17].…”
Section: Discussionsupporting
confidence: 91%
“…Although they remained ambulatory, both dogs demonstrated a progressive clinical course over a short period of around two months, to the point that their owners elected for euthanasia on humane grounds due to their poor quality of life. This history of progression to euthanasia is typical of CCD in most breeds, apart from those with an adult onset and slowly progressive CCD, whereby survival for years is possible [7, 12, 15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is easily implemented in a clinical setting and has been used to assess the recovery of dogs post spinal surgery successfully (Olby and others 2004). There are concerns, however, with reproducibility of rating scales due to their subjective nature (Gordon-Evans and others 2009), observer bias (Arkell and others 2006) and the influence of observer experience on the results (Keegan and others 1998, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Progressive ataxia is the most obvious symptom, with initial disease onset occurring around 3 years to 5 years of age. Visual impairments are not reported and upon examination there is an absence of lipofuscin in the retina.…”
Section: American Staffordshire Terriers – Arylsulfatase Gmentioning
confidence: 99%